Yaşlılarda Besin İlaç Etkileşimi - (:unkn) unknown (My University, 2016)
Dünya yaşlı nüfusu, özellikle gelişmiş ülkelerde,giderek artmaktadır. Yaşa paralel artan kronikhastalıkların tedavisi için yaşlılar daha fazla sayıdailaç kullanmaktadırlar. Beraberinde vücudun değişengereksinimlerını karşılamak / korumak için beslenmedisiplini de ön plana çıkmaktadır. Kronik hastalıklarıntedavisi için kullanılması gereken ilaçlar ve fizyolojikyapıyı korumak için tüketilmesi zorunlu olan besinlerarasında istenmeyen etkileşimlerin olması sözkonusudur. Yaşlanmaya bağlı kognitif, karaciğer,böbrek, mide, bağırsak fonksiyonu ve kasdokusunun azalması, yağ dokusunun artması gibideğişiklikler, etkileşim riskini daha da artırmaktadır.Bu derlemede yaşlılarda olası besin-ilaç etkileşimininincelenmesi ve klinik öneminin vurgulanmasıamaçlanmaktadır

Elderly population has been steadily increasingespecially in developed countries. Elders use multiplemedications for treatment of chronic diseasesincreasing with age. At the same time, nutritionaldiscipline also becomes an issue in order tomeet/protect changing demands of the body. It islikely that undesired interactions occur betweenmedications to be used for treatment of chronicdiseases and food which are essential to maintainthe physiological structure. Changes due to agingsuch as reduction in cognitive, hepatic, renal, gastric,intestinal functions and decreased muscular massand fat tissue further increases the risk ofinteraction. The present compilation aimed atinvestigating and highlighting clinical significance offood-drug interactions in the elderly
Food Drug Interaction in the Elderly
Keywords: Geriatri ve Gerontoloji